Protease of the horse mango (Mangifera foetida Lour) Kernel: Optimum Conditions for Extraction - Ahmad, Mohammad Norazmi; Ibrahim, Izyanti; Yarmo, Mohd Ambar; Said, Mamot (Malaysia Institute of Chemistry, 2013)
Horse mango (Mangifera foetida Lour) fruit is known to produce latex with a blistering effect upon contact with human skin. In this study, it was chosen as a source of protease, and the effect of the extraction process on its protease activity was evaluated. The crude enzyme was extracted from the kernels and extraction was optimized by a response surface methodology (RSM) using a central composite rotatable design (CCRD). Based on the RSM model generated, optimal extraction conditions were obtained at pH 6.0, 8.16 mM CaCl2, 5.0% Triton X-100, and 10.0 mM DTT. Polyvinylpolypyrrolidone (PVPP) and Dowex 2-X8 were added to the medium extraction to remove the polyphenols from the crude extract. The result indicated that, the media which was supplemented with the polyphenols binders acquired the high purified protease compared to the control (media without PVPP and Dowex 2-X8).